Faraday waves in cold-atom systems with two- and three-body interactions - Tomio, Lauro; Gammal, Arnaldo; Abdullaev, Fatkhulla (SpringerLink, 2017)
We report an investigation on Bose-Einstein condensates with two-body (cubic) and three-body (quintic) interactions in the corresponding nonlinear Schrodinger equation, considering s-wave two-body scattering length as periodically varying in time. For the quintic interacting term, the dependence on as was considered within two models, being quadratic or quartic. It was shown that parametric instabilities can lead to the generation of Faraday wave resonances in this system, with wavelengths depending on the background scattering length, as well as on the corresponding modulation parameters. A few sample results are shown here for repulsive as, in case of quadratic and quartic three-body interactions. The effect of dissipation is also verified on the amplitude of the resonances. Analytical predictions for the resonance positions are confirmed by our numerical simulations.